PEMBARUAN KAMPUNG MATI VIETNAM DENGAN PEMBANGUNAN PANTI “JOMPO” DI JAKARTA TIMUR - Melita Michele; F. Tatang H. Pangestu (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
Urbanization which is the movement of people to big cities continues to occur, in the administrative area of ​​DKI Jakarta. According to the Sectoral Statistics of DKI Jakarta Province (2020), East Jakarta has the largest number of immigrants in DKI Jakarta with the total of 2,215 people. Increasing population can increase population density which can then lead to environmental quality degradation. A lot of land in East Jakarta is targeted to build more residential properties than tourist attractions which can attract outsiders to East Jakarta. Applying 'urban acupuncture' can help develop and improve settlement problems experienced in East Jakarta by finding a place that has the potential to be developed. Vietnam's Dead Village is one of the potential areas that is remote, neglected and no longer useful for the environment and the people around this area. The village could be reused as an 'urban acupuncture' intervention to help revive East Jakarta Kampung Mati Vietnam has a history of being the first pilot home for the elderly in Indonesia. Therefore, the renewal of this nursing home program was implemented to restore the memory and history of this place, as well as to overcome the problems that caused the previous nursing home to fail. Furthermore, an urban agriculture program was implemented with the aim of increasing reforestation and independent food production, as well as a trading area as a public program to unite the area around Vietnam's Dead Village. Keywords:   Vietnam’s Dead Village; Nursing Home Abstrak Urbanisasi yang merupakan perpindahan penduduk ke kota besar terus terjadi, Wilayah administrasi DKI Jakarta. Menurut Statistik Sektoral Provinsi DKI Jakarta (2020), Jakarta Timur memiliki jumlah penduduk pendatang terbanyak di DKI Jakarta sebanyak 2.215 jiwa. Meningkatnya jumlah penduduk dapat meningkatkan populasi densitas yang kemudian dapat mengakibatkan degradasi kualitas lingkungan. Lahan di Jakarta Timur banyak ditargetkan untuk membangun properti hunian lebih banyak lagi dari pada tempat wisata untuk menarik masyarakat luar ke Jakarta Timur. Menerapkan ‘akupuntur perkotaan’ dapat membantu mengembangkan dan memperbaiki masalah-masalah permukiman yang dialami Jakarta Timur dengan mencari suatu tempat yang memiliki potensi untuk dikembangkan. Kampung Mati Vietnam adalah salah satu wilayah berpotensi yang terpencil, terbengkalai dan tidak lagi bermanfaat untuk lingkungan dan penduduk di sekitar kawasannya. Kampung tersebut dapat digunakan kembali sebagai intervensi ‘akupuntur perkotaan’ untuk membantu menghidupkan kembali Jakarta Timur. Kampung Mati Vietnam ini memiliki sejarah yang dulunya merupakan percontohan panti jompo pertama di Indonesia. Maka dari itu, diterapkan program panti jompo yang diperbarui untuk mengembalikan memori dan sejarah yang ada pada tempat ini, serta mengatasi masalah-masalah yang membuat panti jompo sebelumnya gagal. Selanjutnya diterapkan program pertanian perkotaan dengan tujuan meningkatkan penghijauan dan produksi bahan pangan mandiri, serta area perdagangan sebagai program publik untuk menyatukan kawasan sekitar Kampung Mati Vietnam ini.